Local Communities’ Perception of Parks And Reserves in Cote d’Ivoire: Do the Wanne People Consider the Monogaga Classified Forest as A Natural Patrimony - Yves, ADOU YAO Constant; Emma, AKE-ASSI; Djakalia, OUATTARA; Edouard, N’GUESSAN Kouakou (Journal of Asian Scientific Research, 2011)
The Parks, Reserves and Classified Forests in Côte d’Ivoire are considered as to-be-conserved national natural patrimony. Their management seldom involves the local communities who live around or inside them. Farming practices exert a continuously high pressure on forest cover. In the case of Monogaga, local people (the Wanne) were allowed to stay in the forest after it had been declared classified. After a period of conflict between the Wanne and SODEFOR, the forest management authority, SODEFOR sought to understand why the Wanne people do not consider the entire forest as a patrimony to conserve and transfer to their children. The present study addresses this question. Local communities recognized several spatial units in the Monogaga Forest. The chiefs of lineage control and guarantee access to those units. In the subdivision of SODEFOR, each zone corresponds to a precise designation: one for agriculture and another one for conservation. For SODEFOR, the forest ecosystems constitute a national patrimony to conserve while taking into accounts land rights and access to resources. For farmers, land that is inalienable and some of its resources (raphia swamp, kporo) constitute a patrimony of the lineage. In the latter case, the use of land and resources obey complexes access rules. Those traditional access rules to land and resources are still in use in Monogaga.